Spatiotemporal Expression and Substrate Specificity Analysis of the Cucumber SWEET Gene Family - Li, Yaxin; Feng, Sheng; Ma, Si; Sui, Xiaolei; Zhang, Zhenxian (Frontiers in Plant Science, 2017)
The functions of SWEET (Sugar Will Eventually be Exported Transporter) proteins have been studied in a number of crops, but little is known about their role in cucumber (Cucumis sativus L.), a model plant for studying stachyose metabolism and phloem function. Here, we identified 17 cucumber SWEET genes (CsSWEETs), located on chromosomes 1 to 6, and classified them into four clades. Two genes from each clade were selected for spatiotemporal expression, subcellular localization and substrate specificity analyses. Clade I and II proteins were all hexose transporters and targeted to the plasma membrane, while clade III proteins also localized to the plasma membrane, but used sucrose as a substrate. Clade IV SWEET proteins were localized to the tonoplast, and used hexose as a substrate. The eight tested CsSWEET genes were most highly expressed in flower, which represents a large sink in plants. However, each gene also showed specific expression patterns: three of the eight tested genes were highly expressed in mature leaves, two in roots, two in fruit, two in stems and one was detected in all tested organs. The likely biological roles of each are discussed based on the above results.